The Level of Handwashing Knowledge and Behavior of Yos Sudarso High School Medan Students' During The COVID-19 Pandemic - Elvira, Cindy; Mariedina, Causa Trisna (TALENTA Publisher, Universitas Sumatera Utara, 2021)
Background: The COVID-19 (Coronavirus Disease 2019) outbreak which was first detected in Wuhan, China, in December 2019, has spread rapidly. One way of preventing and controlling infection in the community is by washing hands thoroughly and regularly. The purpose of this study was to determine the level of handwashing knowledge and behavior of Yos Sudarso High School Medan students’ during the COVID-19 pandemic. Method: The design used was one group pretest-posttest design. The type of data is primary data obtained through online questionnaires using a total sampling technique. Results: Of the 76 respondents, the level of knowledge on handwashing was dominated by the low category, namely 65 people (85.5%) and the good category of handwashing behavior, namely 59 people (77.6%). After being given information, the level of the good knowledge was 35 people (46.1%) and the good behavior was 66 people (86.8%). Students have a low knowledge about handwashing but have a good handwashing intensity behavior during the COVID-19 pandemic. Conclusion: Given information, there is an increase on the level of handwashing knowledge and behavior of Yos Sudarso High School Medan students’ during the COVID-19 pandemic.